Abortion and Capitalism: an analysis of the population policies and economic development in Latin America from the perspective of the Social Reproduction Theory (1950 - 1980) - Luparello, Velia Sabrina (2017)
In the late eighteenth century the direct intervention of the state was strengthened in terms of a biological and social processes, such as: the proportion of births and deaths, the reproduction rate, the fertility of a population, etc. These processes were constituted, in practice, in the object of measurement demographic statistics. They were also the outline of an intervention policy in global phenomena of reproduction and sexuality. Accepting that regulations on sexuality and reproduction existed adopting different ways according to the context, but never being explicit (ie, adopted and adopt the name of “population policy” or “natalist”), one wonders what reasons explain such situation. Thus, this paper aims to analyze, from the theoretical approach of the Social Reproduction Theory, the practice of abortion as a fundamental element in the system of reproduction and production of wage labor. Additionally, this paper looks to understand what kind of relationship it has with demographic and economic development in the second postwar Latin American context.